橋墩振動與基礎孔隙水壓力即時監測系統整合應用研究 - 黃安斌; An-Bin Huang (My University, 2009)
橋樑等跨河構造物，在建造時不但部分結構例如橋墩基礎經常安置在河道內，橋樑兩端之橋臺也會佔據原河道部分之排水斷面，這些因素使得河水流經跨河構造物時流速加快。水與橋墩基礎之互制與快速水流是造成橋墩基礎周圍河床沖刷最主要原因。受台灣氣候、地形與地質特性之影響，暴雨期間河流水位高漲且流速極高，在上游區域則經常觸發土石流使得河川洪水具有高泥沙含量。此高泥沙含量洪水可將巨石浮起，順溪流向下沖刷，造成更大之衝擊與破壞力。本計劃將於單一橋墩基礎上下游側單一鑽孔內不同深度安裝多個封裝於高強度鋼管內之水壓計與在橋墩結構上安置傾角/加速度儀，並於鄰近岸邊橋臺外監測機房內安裝資料解讀與訊號傳輸系統，綜合探討孔隙水壓力對總體破壞之機制與量測孔隙水壓力之變化來推測橋墩鄰近基礎之沖刷深度。本計畫完成後，將可以提供橋樑管理單位在洪水來臨或地震發生時的即時監測資料，以即時的資訊對封橋的時間做彈性與最佳之掌控，並以最便民的條件下，保護用路人的安全避免生命或財產的損失，另外水壓計與傾角/加速度儀的安裝可以收集到鄰橋墩基礎附近水壓與結構行為等資料，這些資料加以整合與分析，將有助於日後新橋樑興建或既有橋樑補強的分析與設計。

Parts of the river-crossing structures such as bridge piers are often placed within the river channel. These structural elements along with the approaching ramps reduce the original sectional area of the river and cause the flow rate to increase. The interaction between water and bridge pier foundations and high flow rate are the main reasons for local scouring. Affected by the weather and land formation/geology, the water level and flow rate are usually very high during heavy rain falls. These conditions tend to trigger mudflows in the upstream areas and result in high mud-content in the flood water. The high mud-content flow is capable of floating boulders and transporting them downstream under high speed, creating massive impact and destructive forces. This research project plans to install an array of pore water pressure sensors respectively at the upstream and downstream side of a bridge pier foundation. The pressure sensors sealed within a steel pipe will be used to monitor the distribution pore water pressure at different depths. A set of inclination and acceleration sensors will be placed on the bridge pier. All sensors will be connected to a data logging/transmission set up located outside of the bridge. The depth of scour during a flood period will then be evaluated using the collected pore water pressure data. Techniques developed in this project will offer real time information to the bridge management team in periods of flood or earthquake for optimized control of the bridge usage and to offer maximum protection to the bridge users. The instrumentation will enable information regarding the structural behavior of a bridge via long term collection of inclination/acceleration and pore-water pressure measurement data. The compilation and analysis of these data will help in the design of new bridges or rehabilitation of the old.
Integration and Field Deployment of a Realtime Bridge Pier Vibration and Foundation Soil Pore Water Pressure Monitoring System
Keywords: 橋墩; 振動; 基礎沖刷; bridge pier; vibration; foundation scour